Gender Wage Differentials in a Competitive Labor Market: The Household Interaction Effect - Patrick Francois; Jan C. van Ours (Institute for the Study of Labor (IZA), 2000)
We present a theoretical explanation of the gender wage gap which turns on the interaction between men and women in households. In equilibria where men are over-represented in fulltime work, we show that firms rationally choose to hire women only at strictly lower wages than men. The model developed predicts a gap even controlling for education, occupation and industry of workers and does so in a competitive labor market where there exist no inherent gender differences. We test our theory using CPS data over the period 1979-98 and find it is strongly supported by the data.
Keywords: J41; J16; J71; 330; Gender discrimination; household models; wage gap; Lohndifferenzierung; Geschlecht; Haushaltsökonomik; Humankapital; USA